1999
DOI: 10.1002/(sici)1096-9845(199912)28:12<1541::aid-eqe880>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Bi-directional pseudodynamic test of a full-size three-storey building

Abstract: SUMMARYThe reliability of a Pseudodynamic (PsD) test depends primarily on the accuracy of the control system. Di$culties arise mainly when the method is applied to very sti! or very heavy structures or to structures with a high number of Degrees of Freedom (DoFs). This paper describes the bi-directional PsD testing of a full-size three-storey building. The tested specimen is a composite structure with plan dimensions of 12;16 m and height of 9)5 m, made of steel columns and beams combined with composite reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 4 publications
2
31
0
Order By: Relevance
“…columns) and the collapse load may be overestimated when gravity loads are not physically applied. In a substructured PsD test, the equation of motion can be written in discretised form as: Developments in multi-axis substructure testing have also been made using multiaxial actuators with uni-directional rotation or three-dimensional rotational hinges ( [21], [22], [23], [24], [25], [26], [27] & [28]). The multi-directional displacements of the test structure are taken into account by co-ordinate transformation methods based on trigonometry.…”
Section: Substructured Pseudo Dynamic Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…columns) and the collapse load may be overestimated when gravity loads are not physically applied. In a substructured PsD test, the equation of motion can be written in discretised form as: Developments in multi-axis substructure testing have also been made using multiaxial actuators with uni-directional rotation or three-dimensional rotational hinges ( [21], [22], [23], [24], [25], [26], [27] & [28]). The multi-directional displacements of the test structure are taken into account by co-ordinate transformation methods based on trigonometry.…”
Section: Substructured Pseudo Dynamic Test Methodsmentioning
confidence: 99%
“…Molina et al, [22] performed bi-directional PsD testing of full-scale three-storey building at the Joint Research Centre, Ispra, Italy, as shown in Figure 13 Pegon and Pinto, [19] discuss general developments in PsD substructured testing of a full-scale bridge structure at the ELSA Laboratory at Ispra, Italy. Notably, the paper investigates the topic of asynchronous testing.…”
Section: Figure 13 Generalised Floor Plan Of Bi-directional Psd Testmentioning
confidence: 99%
“…Thus, a geometric transformation between these co-ordinate systems is necessary. It is performed on-line during testing according to the algorithm developed at the ELSA laboratory of the European Commission JRC [36]. In the PsD test method it is not necessary to add masses to the test structure.…”
Section: Pseudodynamic Testingmentioning
confidence: 99%
“…The tests were carried out in ELSA in July 2003 by means of the pseudodynamic method [4][5][6][7], which makes it possible to overcome the limitations of weights and dimensions, which are associated with the use of shaking tables. In order to reproduce in the columns the design values of the axial loads, a total vertical load of 600 kN was applied by means of vertical jacks, as shown in Fig.…”
Section: Experimental Structure and Experimentation Programmementioning
confidence: 99%